A flame retardant polyamide composite material and its preparation method and application
By introducing polyvinylpyrrolidone into halogen-free flame-retardant polyamide composite materials and optimizing the formulation, the problems of halogen-free flame-retardant polyamide composite materials in appearance and precipitation performance are solved, and the flame-retardant and appearance performance are improved, which is suitable for the preparation of electronic and electrical shells.
Patent Information
- Application Number
- CN202111611123.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-12-27
AI Technical Summary
Halogen-free flame-retardant polyamide has problems in appearance and precipitation performance, which limits its wide application in low-voltage electrical appliances, new energy and automobiles.
By introducing polyvinylpyrrolidone into the halogen-free flame retardant polyamide composite and optimizing the content of other components in the formulation, including hypophosphite flame retardant, melamine polyphosphate and borate flame retardant synergist, combined with the extrusion process of the twin screw extruder, composite materials with good appearance and low precipitation performance are prepared.
The flame retardant and appearance performance of halogen-free flame retardant polyamide composite materials have been improved, the precipitation of melamine polyphosphate is reduced, the impact performance of the material is improved, and it is suitable for the preparation of electronic and electrical shells.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a flame retardant polyamide composite material and a preparation method and application thereof. Background Art
[0002] Halogen-free flame-retardant polyamide is widely used in low-voltage electrical appliances, new energy, and automobiles due to its excellent flame-retardant properties, mechanical properties, electrical properties, low smoke and toxicity, and environmental protection. However, compared with other flame-retardant polyamides, halogen-free flame-retardant polyamide has problems such as poor appearance and precipitation after long-term storage, which seriously limits its wide application.
[0003] In order to solve the appearance problem of organic phosphine flame retardant polyamide, the commonly used method is to improve the fluidity of the material. Although there is a certain improvement, the effect is limited, and flash is easily formed during the injection molding process. Studies have found that the surface precipitation problem of halogen-free flame retardant polyamide is mainly caused by melamine polyphosphate. The most commonly used method at present is to reduce the content of melamine polyphosphate, or even not use melamine polyphosphate, but melamine polyphosphate is an important component of halogen-free flame retardant, and its content has a crucial influence on the flame retardant properties of halogen-free flame retardant polyamide. Chinese patent CN108976471 A improves the flame retardant properties of halogen-free flame retardant polyamide composites and reduces the content of melamine polyphosphate by introducing organosilicon synergists, thereby improving the precipitation properties of the material. But in general, although the surface precipitation has improved, it still exists and will deteriorate the impact properties of the material. In addition, this solution is not applicable to industries with strict silicon control such as household appliances. In the field of engineering applications, Klein has developed a new type of organic phosphine flame retardant, named OP 1400, to replace the OP 1230 / MPP solution to prepare low-precipitation halogen-free flame-retardant polyamide composite materials. However, OP 1400 has low flame retardant efficiency, large addition amount, and will reduce the flow properties of the material, thereby deteriorating the appearance of the halogen-free flame-retardant polyamide composite materials.
[0004] When glass fiber is reinforced, floating fiber defects are prone to occur, especially when the resin crystallizes too quickly, which aggravates the defect.
[0005] Therefore, developing a halogen-free flame-retardant polyamide composite with good appearance and low precipitation is of great significance to broadening the application of halogen-free flame-retardant polyamide. Summary of the invention
[0006] The object of the present invention is to provide a flame retardant polyamide composite material, which has the advantages of good flame retardancy and good appearance.
[0007] Another object of the present invention is to provide a preparation method and application of a flame retardant polyamide composite material.
[0008] The present invention is achieved through the following technical solutions:
[0009] A flame retardant polyamide composite material, comprising the following components in parts by weight:
[0010] 60 parts of polyamide resin;
[0011] 1-6 parts of polyvinyl pyrrolidone;
[0012] 8-30 parts of hypophosphite flame retardant;
[0013] Melamine polyphosphate 0.5-2 parts;
[0014] 1-5 parts of borate flame retardant synergist;
[0015] 10-40 parts of glass fiber.
[0016] Preferably, the following components are included by weight:
[0017] 60 parts of polyamide resin;
[0018] 2-4 parts of polyvinyl pyrrolidone;
[0019] 12-20 parts of hypophosphite flame retardant;
[0020] Melamine polyphosphate 0.8-1.5 parts;
[0021] 1.5-3 parts of borate flame retardant synergist;
[0022] 10-40 parts of glass fiber.
[0023] The polyamide resin is selected from at least one of PA6, PA56, PA66, PA6 / 66, PA66 / 6, PA66 / 6T, PA6T / 66, and MXD6.
[0024] The number average molecular weight of the polyvinyl pyrrolidone is 8000-800000 g / mol, preferably 12000-220000 g / mol.
[0025] The hypophosphite flame retardant is selected from at least one of aluminum hypophosphite and diethyl aluminum hypophosphite.
[0026] Preferably, the average degree of polymerization of the melamine polyphosphate is 100-300.
[0027] The borate flame retardant synergist is selected from at least one of zinc borate, magnesium borate and aluminum borate.
[0028] Whether to add 0-1 part of antioxidant can be determined according to actual needs. It can be a hindered phenol antioxidant.
[0029] The preparation method of the flame retardant polyamide composite material of the present invention comprises the following steps: according to the proportion, each component is uniformly mixed and then extruded and granulated by a twin-screw extruder, the screw temperature range is 200-280°C, and the rotation speed range is 250-350rpm, so as to obtain the flame retardant polyamide composite material.
[0030] The flame retardant polyamide composite material of the present invention is used for preparing electronic and electrical appliance housings.
[0031] The present invention has the following beneficial effects:
[0032] First, polyvinyl pyrrolidone can promote carbonization and improve the quality of the carbon layer. Therefore, when the content of melamine polyphosphate is low, the vertical combustion performance of halogen-free flame retardant polyamide can still reach 0.8mmV-0 by introducing an appropriate amount of polyvinyl pyrrolidone.
[0033] Secondly, on the one hand, the presence of polyvinyl pyrrolidone can reduce the amount of melamine derivatives used, thereby reducing the amount of precipitation of the flame retardant; on the other hand, polyvinyl pyrrolidone within a certain molecular weight range can reduce the precipitation of melamine derivatives.
[0034] Third, the carbonyl group of polyvinyl pyrrolidone forms hydrogen bonds with polyamide molecules, reducing the crystallization rate of polyamide, thereby further improving the appearance of the product. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0036] The sources of raw materials used in the embodiments and comparative examples are as follows:
[0037] PA66, grade PA66 EP-158, Huafeng Group;
[0038] PA6, brand PA6 HY-2800, Haiyang Chemical Fiber Company;
[0039] PA56, grade 1270W, Cathay Co., Ltd.;
[0040] PA66 / 6T, brand C1504T, Guangyin Co., Ltd.;
[0041] Glass fiber, grade ECS10-3.0-568H, China Jushi Co., Ltd.;
[0042] Diethyl aluminum hypophosphite, grade OP 1230, Klein Company;
[0043] Aluminum hypophosphite: Brand M-116S, Shanghai Lidao New Materials Technology Co., Ltd.
[0044] Melamine polyphosphate-1, brand MPP-1, degree of polymerization 50, Budenheim Iberica, Germany;
[0045] Melamine polyphosphate-2, brand MPP-2, polymer 100, Budenheim Iberica, Germany;
[0046] Melamine polyphosphate-3, brand MPP-3, degree of polymerization 300, Budenheim Iberica, Germany;
[0047] Melamine polyphosphate-4, brand MPP-4, degree of polymerization 400, Budenheim Iberica, Germany;
[0048] Zinc borate, brand ZB-503, Anhui Yishitong Co., Ltd.;
[0049] Polyvinylpyrrolidone A, number average molecular weight 12000 g / mol, Shanghai Kema Company;
[0050] Polyvinylpyrrolidone B, number average molecular weight 40000 g / mol, from Shanghai Kema Company;
[0051] Polyvinylpyrrolidone C: number average molecular weight 220000 g / mol, Shanghai Kema Company;
[0052] Polyvinylpyrrolidone D: number average molecular weight 600000 g / mol, from Shanghai Kema Company;
[0053] Antioxidant: Antioxidant 1010, commercially available.
[0054] Performance testing method:
[0055] (1) Flame retardant performance: The flame retardant performance of the sample was tested according to the relevant standards of UL 94-2013, and the sample thickness was 0.8 mm. Flame retardant performance is of great significance to electrical safety. The UL94 flame retardant grade needs to reach V-0 to meet application requirements.
[0056] (2) Appearance: Injection molded color plates (84*54*2.0mm) are inspected for floating fibers on the surface of the plates. The plates are evaluated based on the floating fibers on the surface of the plates. The results are divided into four levels: no floating fibers, inconspicuous floating fibers (less than 5 fibrous protrusions and the protrusions are shallow, which do not affect the appearance of the plate surface), obvious floating fibers (about 5-10 fibrous protrusions and the protrusions are high, which can only maintain a good appearance), and many floating fibers (the number of protrusions on the surface of the plate is greater than 10, which has obviously affected the appearance of the plate surface).
[0057] (3) Precipitation performance: For injection molded color plates, treat the color plates in a double 85 degree heat and humidity aging oven for 168 hours, and observe whether there is white precipitate on the surface of the color plate. According to the precipitation situation, four levels are divided into: no precipitation, inconspicuous precipitation (there are less than 4 light white spots on the color plate), obvious precipitation (the light white spots on the color plate are larger, and some spots are connected to each other), and more precipitation (there are white precipitates in pieces on the color plate).
[0058] Table 1: Content (parts by weight) of each component of flame-retardant polyamide composite materials and test results of Examples 1-6
[0059] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 PA66 60 60 60 PA6 60 PA56 60 PA66 / 6T 60 Glass Fiber 30 30 30 30 10 40 Diethylaluminum hypophosphite 15 15 15 15 30 8 Melamine Polyphosphate-2 1 1 1 1 0.5 2 Zinc borate 2 2 2 2 1.5 3 Polyvinylpyrrolidone B 3 3 3 3 6 1 Vertical combustion performance V-0 V-0 V-0 V-0 V-0 V-0 Appearance No floating fibers No floating fibers No floating fibers No floating fibers No floating fibers Floating fibers are not obvious Separation No precipitation No precipitation No precipitation No precipitation No precipitation No precipitation
[0060] It can be seen from Example 5 that when the addition amount of diethylaluminum hypophosphite reaches 30 parts, its precipitation can also be suppressed.
[0061] It can be seen from Example 6 that, under the formulation of the present invention, the amount of glass fiber added can reach 40 parts and the floating fiber can be controlled within a very small range.
[0062] Table 2: Content (parts by weight) of each component of flame-retardant polyamide composite materials of Examples 7-13 and test results
[0063] Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Example 13 PA66 60 60 60 60 60 60 60 Glass Fiber 30 30 30 30 30 30 30 Diethylaluminum hypophosphite 12 20 8 30 15 15 15 Melamine Polyphosphate-2 1.5 0.8 2 0.5 Melamine polyphosphate-1 1 Melamine Polyphosphate-3 1 Melamine Polyphosphate-4 1 Zinc borate 3 1.5 5 1 2 2 2 Polyvinylpyrrolidone B 4 2 1 6 3 3 3 Vertical combustion performance V-0 V-0 V-0 V-0 V-0 V-0 V-0 Appearance No floating fibers No floating fibers No floating fibers Floating fibers are not obvious No floating fibers No floating fibers Floating fibers are not obvious Separation No precipitation No precipitation No obvious precipitation No precipitation No obvious precipitation No precipitation No precipitation
[0064] It can be seen from Examples 1 / 7-10 that the appearance is better within the preferred ratio range.
[0065] It can be seen from Examples 1 / 11-13 that the average degree of polymerization of melamine polyphosphate is preferably 100-300.
[0066] Table 3: Content of each component (parts by weight) and test results of flame-retardant polyamide composite materials of Examples 14-16
[0067] Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 PA66 60 60 60 60 60 Glass Fiber 30 30 30 30 30 Diethylaluminum hypophosphite 15 15 15 15 Aluminum Hypophosphite 15 Melamine Polyphosphate-2 1 1 1 1 1 Zinc borate 2 2 2 2 2 Polyvinylpyrrolidone A 3 3 3 Polyvinylpyrrolidone C 3 Polyvinylpyrrolidone D 3 Flame retardants Vertical combustion performance V-0 V-0 V-0 V-0 V-0 Appearance No floating fibers No floating fibers Floating fibers are not obvious No floating fibers No floating fibers Separation No precipitation No precipitation No precipitation No precipitation No precipitation
[0068] It can be seen from Examples 1 / 14-16 that the preferred number average molecular weight is 12000-220000 g / mol.
[0069] Table 4: Content of each component (parts by weight) and test results of comparative flame-retardant polyamide composite materials
[0070] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 PA66 60 60 60 60 60 60 Glass Fiber 30 30 30 30 30 30 Diethylaluminum hypophosphite 15 15 15 15 15 15 Melamine Polyphosphate-2 1 1 0.1 2.5 1 1 Zinc borate 2 2 2 2 0.5 6 Polyvinylpyrrolidone A 0.5 8 3 3 3 3 Vertical combustion performance V-1 V-0 V-1 V-0 V-1 V-0 Appearance More floating fibers More floating fibers No floating fibers Floating fibers are not obvious No floating fibers More floating fibers Separation No precipitation No precipitation No precipitation Clear precipitation No precipitation No precipitation
[0071] It can be seen from comparative example 1 / 2 that when the addition amount of polyvinyl pyrrolidone is too low, the flame retardant performance of the halogen-free flame retardant polyamide composite cannot reach V-0, and there are more floating fibers on the surface; when the amount of polyvinyl pyrrolidone is more, the flame retardant performance of the halogen-free flame retardant polyamide composite can reach V-0, but there are more floating fibers on the surface. The possible reason is that its thermal stability is poor, resulting in more gas during the injection molding process of the material, making it impossible for the melt to replicate the mold well.
[0072] It can be seen from comparative examples 3 / 4 that when the amount of melamine polyphosphate added is too low, the flame retardant performance of the halogen-free flame retardant polyamide composite cannot reach V-0; when the amount of melamine polyphosphate added is too high, there is obvious precipitation on the surface of the halogen-free flame retardant polyamide composite. This is because melamine polyphosphate has poor compatibility with polyamide and is prone to migrate outward when the content exceeds a certain amount.
[0073] It can be seen from Comparative Examples 5 / 6 that if the amount of borate flame retardant synergist added is too low, the flame retardant performance of the halogen-free flame retardant polyamide composite cannot reach V-0; if the amount of borate flame retardant synergist added is too high, there will be more floating fibers on the surface of the halogen-free flame retardant polyamide composite. This is because if the amount of borate flame retardant synergist added is too high, the viscosity of the melt will be reduced, resulting in the melt being unable to replicate the mold and cover the surface glass fiber well.
Claims
1. A flame retardant polyamide composite material, characterized in that: By weight, it includes the following components: 60 parts of polyamide resin; 1-6 parts of polyvinyl pyrrolidone; 8-30 parts of hypophosphite flame retardant; Melamine polyphosphate 0.5-2 parts; 1-5 parts of borate flame retardant synergist; Glass fiber 10-40 parts; The number average molecular weight of the polyvinyl pyrrolidone is 8000-800000 g / mol.
2. The flame retardant polyamide composite material according to claim 1, characterized in that: The polyamide resin is selected from at least one of PA6, PA56, PA66, PA66 / 6, PA66 / 6T, and MXD6.
3. The flame retardant polyamide composite material according to claim 1, characterized in that: The number average molecular weight of the polyvinyl pyrrolidone is 12000-220000 g / mol.
4. The flame retardant polyamide composite material according to claim 1, characterized in that: The average degree of polymerization of melamine polyphosphate is 100-300.
5. The flame retardant polyamide composite material according to claim 1, characterized in that: The hypophosphite flame retardant is selected from at least one of aluminum hypophosphite and diethyl aluminum hypophosphite.
6. The flame retardant polyamide composite material according to claim 1, characterized in that: The borate flame retardant synergist is selected from at least one of zinc borate, magnesium borate and aluminum borate.
7. The flame retardant polyamide composite material according to claim 1, characterized in that: By weight, 0-1 part of antioxidant is also included.
8. The method for preparing the flame retardant polyamide composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating the components through a twin-screw extruder, wherein the screw temperature range is 200-280°C and the rotation speed range is 250-350rpm, so as to obtain a flame-retardant polyamide composite material.
9. Use of the flame retardant polyamide composite material according to any one of claims 1 to 7, characterized in that: Used to prepare electronic and electrical housings.
Citation Information
Patent Citations
Flame retardant complex system and halogen-free flame-resistant resin-based composite material containing same
CN108976471A
Wet and heat ageing resistance separated halogen-free flame retardance nylon composite material
CN109467925A
Fire-retardant polyamides comprising pvp
CN110446756A